Influence of nucleotomy on the load sharing in the spinal facet joint under the loading scenarios of different human postures. (July 2021) - Lu, Yongtao; Cheng, LiangLiang; Zhu, Hanxing
Highlights: The influence of the intervertebral disc (IVD) nucleotomy on the load sharing in the spinal facet joint under the loading scenarios of different human postures was performed. After the IVD nucleotomy, the forces in the facet joints are significantly increased under the postures of upright, 5° extension and 5° flexion. The IVD nucleotomy can cause an increase in the overall forces in the facet joint and may serve as a possible explanation for the low back pain. Abstract: One-in-five people suffer from chronic low back pain (LBP). The incidence of this disease has doubled since 1950s and affects not only the elderly, but also the young population. However, the mechanism of LBP is still unknown. A possible location where the LBP may develop is the facet joint and it has been revealed that the intervertebral disc (IVD) nucleotomy may be a trigger for LBP. The aim of the present study was to investigate the influence of IVD nucleotomy on the load sharing in the spinal facet joint under the loading scenarios of different postures. Finite element (FE) models of the intact and nucleotomised L4 – L5 spinal segments were generated from the clinical CT images. Seven human postures, including upright, 5° extension, 5° flexion, ± 6° lateral bending and ± 2° axial rotation, were simulated. The resultant forces in the fact joint were compared between the intact and the nucleotomised cases. It was revealed that the IVD nucleotomy significantly increased the forces in the facet joints under the loading scenarios of upright, 5° extension and 5° flexion. The IVD nucleotomy increased the force in the ipsilateral facet joint but decreased the force on the contralateral side under the loading scenarios of ± 2° axial rotation. However, the IVD nucleotomy made little influence on the resultant forces in both facet joints in the postures of ± 6° lateral bending. In conclusion, the IVD nucleotomy can cause an increase in the overall force in the facet joint, and thus may serve as a possible explanation for the LBP and a main contributing factor for the pain complaints.